KERENTANAN SOSIAL EKONOMI AKIBAT KENAIKAN MUKA AIR LAUT - Awanda Sentosa (Jurnal Kajian Pengembangan Perkotaan, 2012)
The sea level rise in coastal areas in the north of Jakarta has been a phenomenon of urban life. Its presence brings a pool of water that poses some problems for the residents of the city. The purpose of this paper is to examine the socio-economic vulnerability of those residents to the sea level rise. The method used is Cluster Random Sampling and for the calculation of the index of socio-economic vulnerability to the sea level rise, the writer used the Socio-Economic Vulnerability Index formula. The results of this research show that there are forms of physical and non-physical adaptations of this group of people